The Interaksi Media Sosial Terhadap Niat Beli Merek Produk Fashion Lokal ‘Erigo’: Pengaruh Kredibilitas Sumber, Homofili Sumber, Dan Kualitas Konten Sebagai Variabel Mediasi - Fadhil Rahmadani; Anas Hidayat (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to analyze the factors influencing social media interaction regarding the purchase intention of the local fashion brand Erigo. The methodology employed in this study utilizes a quantitative approach with purposive sampling techniques. The criteria for respondents in this research are active Instagram users from the millennial and Generation Z cohorts, aged 19-36, residing in Indonesia. The valid number of respondents is 150. Data processing is carried out using the PLS-SEM method. The variables examined in this study include social media interaction, source credibility, source homophily, content quality, and purchase intention. The findings of this research indicate that social media interaction has a positive influence on source credibility, source homophily, and content quality. Source homophily and content quality positively affect purchase intention. However, source credibility does not have a significant impact on purchase intention. The results of this research are expected to assist companies and marketers in developing more intimate relationships with consumers and encouraging consumer intent to purchase through social media interaction.